Structure and properties of chemically synthesized BiFeO3. Influence of fuel and complexing agent - Ilic, Nikola I.; Dzunuzovic, Adis S.; Bobic, Jelena D.; Stojadinovic, Bojan S.; Hammer, Peter [UNESP]; Petrovic, Mirjana M. Vijatovic; Dohcevi-Mitrovic, Zorana D.; Stojanovic, Biljana D. (Elsevier B.V., 2015)
Perovskite, single multiferroic bismuth ferrite was prepared by two chemical methods: auto-combustion and soft chemical route. Influence of different fuels and complexing agents and thermal treatment on purity of bismuth ferrite powders and density of bismuth ferrite ceramics were investigated. X-ray diffraction technique (XRD) indicated that optimal temperatures and times for calcination and sintering are 600 degrees C for 2 h and 800 degrees C for 1 h with quenching, respectively. Scanning electron microscopy (SEM) analysis showed that soft route synthesized samples formed softer agglomerates and smaller grains with less secondary phases. Powders and pellets were characterized by Brunauer Emmett Teller (BET) specific surface area analysis, particle size distribution, Fourier transform infrared spectroscopy (FT-IR), dilatometry, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), dielectric and magnetic measurements. Resistivity and origin of electrical resistance were studied by means of impedance measurements. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Powders: chemical preparation; Electron microscopy; X-ray methods; Bismuth ferrite